Ceramika z Bolesławca — dziedzictwo w tranzycie - Kurpiel, Anna; Maniak, Katarzyna (Kultura i Społeczeństwo, 2020)
This article analyses the phenomenon of stenciled ceramics from Bolesławiec, a city in Lower Silesia, which was annexed to Poland after the Second World War. On the basis of theories from the field of cultural heritage, memory studies, and economics, the authors trace the discrepancy between the modern view of these ceramics and their social and historical biography. As a result, they propose the use of two new terms, “heritage with multiple heirs” and the “economy of (non)memory,” which would help people to understand this multidimensional phenomenon and would encompass the appropriation of cultural heritage, the negotiation of its meanings, and the role of cultural heritage in a neoliberal economy.